1986
DOI: 10.1002/jcp.1041280218
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic and biochemical variability of tissue and cultured cells from human pheochromocytoma

Abstract: Primary cell cultures from 18 human pheochromocytomas were maintained in culture for 10 to 12 days and characterized. The cell yields ranged from 1.0 to 60.1 X 10(6) cells/g wet weight of tissue. Cell size, as determined by histofluorescent microscopy, varied as much as seven-fold among cells derived from a given tumor and ten-fold between cells from all tumors. Cell catecholamine content, norepinephrine (NE) plus epinephrine, ranged from 0.4 to 89.5 nmol/10(6) cells at day 5 in culture and did not correlate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
(37 reference statements)
1
3
0
Order By: Relevance
“…In addition, and in a similar way to that previously described by other authors (Tischler et al, 1984;Jaques and Tobes, 1986), we have observed a decrease in catecholamine levels with the progression of the culture. The decrease in norepinephrine, epinephrine and dihydroxyphenylglycol observed in cell cultures does not seem to be related to a dedifferentiation process as catecholamine precursors, DOPA and dopamine did not increase concomitantly.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In addition, and in a similar way to that previously described by other authors (Tischler et al, 1984;Jaques and Tobes, 1986), we have observed a decrease in catecholamine levels with the progression of the culture. The decrease in norepinephrine, epinephrine and dihydroxyphenylglycol observed in cell cultures does not seem to be related to a dedifferentiation process as catecholamine precursors, DOPA and dopamine did not increase concomitantly.…”
Section: Discussionsupporting
confidence: 87%
“…As for the cell content in culture with the passing of time, results shown in the literature are somehow contradictory. On the one hand a marked loss of cells after 21 days in culture has been demonstrated (Tischler et al,1984) while on the other no loss of cells over a period of 12 days in culture has been shown (Jaques and Tobes, 1986). In our experimental conditions -5 days in culture -no change in cell content was observed.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations